Decadal-scale variability of sardine and anchovy simulated with an end-to-end coupled model of the Canary Current ecosystem. (February 2019) - Sánchez-Garrido, J.C.; Werner, F.E.; Fiechter, J.; Rose, K.A.; Curchitser, E.N.; Ramos, A.; García Lafuente, J.; Arístegui, J.; Hernández-León, S.; Rodríguez Santana, A.
Highlights: End-to-end ecosystem model for sardine and anchovy in the Canary Current. Synchronous decadal-scale variability of sardine and anchovy. Sardine and anchovy recruitment success primarily linked to food availability. Synchronous effect of large-scale variation of plankton and temperature. Particular vulnerability of anchovy larvae to wind-driven advection. Abstract: Small pelagic fish species, such as sardine and anchovy, can exhibit dramatic decadal-scale shifts in abundance in response to climate variability. Understanding the mechanisms and the relationships among the different components of the food web through which environmental forcing can drive the observed fish variability remains a challenging problem. The modelling study described herein, focusing on the Canary Current System, implements and builds on earlier modelling efforts by Rose et al. (2015) and Fiechter et al. (2015) in the California Current System. This new application of the modelling framework to the Canary Current system provides an approach that bridges a comprehensive database with end-to-end (climate-to-fish) modelling, thereby enabling the investigation of the sources of variability of sardine ( Sardina pilchardus ) and anchovy ( Engraulis encrasicolus ). The aim of the modelling effort is to gain insights into the underlying mechanisms that drive the observed biological variability. Particular attention is given to the absence of regime shifts between sardine and anchovy in the Canary Current, which is a distinctive feature among the four major eastern boundary upwelling ecosystems. A model simulation for 1958–2007 was performed and analysed. The biological traits and behaviours prescribed for sardine and anchovy for the Canary Current give rise to different spatial distribution of their populations, and in contrast with other eastern boundary upwelling ecosystems, to synchronous (rather than asynchronous) variability of their abundance and biomass. Analyses of years with anomalously high increases and declines of the adult populations implicate food availability (instead of temperature or other environmental drivers) as the main factor determining recruitment for both sardine (via spawning and survival of feeding age-0 individuals) and anchovy (via survival of feeding age-0 individuals). The common dependence of sardine and anchovy on food, together with the domain-wide response of zooplankton to climate forcing generated in the model, provides a plausible explanation for the synchronization of the two populations. Our results also point at differences between sardine and anchovy; while the two species thrive under enhanced upwelling-favourable winds, anchovy larvae become particularly vulnerable to drift mortality, and thus do better than sardine under more moderate upwelling conditions.